TOOTHPASTES COMPOSITION AND THEIR ROLE IN ORAL CAVITY HYGIENE - Maria-Alexandra Martu; Simona Stoleriu; Liliana Pasarin; Daniela Tudorancea; Ioana-Andreea Sioustis; Ionut Taraboanta; Darius Sandu; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2021)
Toothpaste formulas have evolved over time. Today they contain about 20 ingredients. Toothpastes normally contain: active ingredients, abrasives, surfactants, gelling agents, buffers, flavors and sweeteners, dyes and preservatives, water, moisturizers. Among these ingredients are compounds that fight and prevent the appearance of carious lesions, gingival diseases, halitosis, calculus, dental erosions, staining and dentinal hypersensitivity. Herbal toothpastes, which contain natural antibacterial agents, are a good alternative to reduce the risk of oral conditions in both children and adults.